Actuator fault estimation based adaptive polytopic observer for a class of LPV descriptor systems. (8th September 2014) - Rodrigues, M.; Hamdi, H.; Theilliol, D.; Mechmeche, C.; BenHadj Braiek, N.; Casavola, Alessandro; Rodrigues, Mickael; Theilliol, Didier
Summary This paper presents an Adaptive Polytopic Observer (APO) design in order to develop an actuator fault estimation method dedicated to polytopic Linear Parameter Varying (LPV) descriptor systems. This paper extends a fault diagnosis method developed for regular LTI systems to polytopic LPV descriptor systems. Here, time‐varying actuator faults are also considered, whereas in many papers, actuator faults are generally assumed to be constant. The design and convergence conditions of this APO are provided. The design is formulated through LMI techniques under equality constraints. The performances of the proposed actuator fault estimation scheme are illustrated using an electrical circuit. Copyright © 2014 John Wiley & Sons, Ltd.